FOMO AND AI ADOPTION : AN IN-DEPTH ANALYSIS OF DECISION-MAKING DRIVERS - Jehlička, Jakub; Špaček, Miroslav, 1954-; Busch, Thorsten; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This study investigates the influence of personal characteristics on the adoption of emerging technologies, with a focus on Artificial Intelligence (AI). It explores how the Fear of Missing Out (FOMO) impacts decision-making among decision makers which has so far not been extensively studied. While AI offers significant benefits in enhancing productivity and innovation, the pressure to adopt these technologies come from multiple directions creating a hype with often evoking FOMO, which can lead to impulsive and suboptimal decisions. The research highlights that decision-makers with extensive hands-on experience and a deep understanding of AI tend to exhibit lower levels of FOMO, enabling them to make more rational and strategic decisions. Conversely, those with higher FOMO are more likely to rush into AI adoption, influenced by competitive pressures and the fear of falling behind. The study employs a qualitative methodology, conducting semi-structured interviews with decision-makers from diverse industries. The findings reveal a complex interplay between personal traits, such as experience, tolerance for ambiguity, and emotional resilience, and external factors like competitive dynamics and technological advancements. These factors collectively shape how decision-makers approach the adoption of AI technologies. The research underscores the need for organizations to develop strategies that mitigate the influence of FOMO, ensuring that technology adoption decisions are based on thorough evaluation rather than reactive impulses. The study's insights contribute to a deeper understanding of the psychological factors that drive technology adoption, offering valuable guidance for business leaders navigating the challenges of AI integration in their organizations.
Vedoucí práce: Miroslav Špaček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses